Pediatric Thoracic Surgery at Bangladesh Shishu Hospital & Institute: An Eighteen-Month Clinical Experience (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Pediatric thoracic surgery accounts for characteristic difficulties due to its diverse range of congenital and acquired conditions, and largely affected by infectious diseases, like empyema thoracic in developing countries. The scenario is far more challenging in resource-constrained settings like Bangladesh, where the outcome is often influenced by late presentation and limited logistics.Objective: This study aims to evaluate the surgical experience and outcomes of pediatric thoracic procedures in a tertiary pediatric hospital in Bangladesh. Methods & Methods: This retrospective observational study conducted at the Department of Pediatric Thoracic Surgery, Bangladesh Shishu Hospital & Institute, Dhaka, Bangladesh from October 2024 to March 2026.  Total 91 patients aged 0-12 years undergoing thoracic surgery were included. Dataregarding demographics, clinical presentation, diagnosis, surgical intervention, postoperative complications, and 3-month follow-up outcomes were analyzed.Results: The mean age was 3.8 ± 2.6 years, with a male predominance (63.7%). The most common presenting symptoms were fever (63.7%), respiratory distress (57.1%), and cough (51.6%). Infectious conditions accounted for the majority (71.5%), followed by congenital anomalies (18%).The most common procedures were open decortication (37.5%) and chest drain insertion (31.9%) and, with limited use of VATS (2.2%). Right-sided involvement was more frequent 60.4%vs 39.6% left-sided.Postoperative complications occurred in 14.3%of patients, most commonly surgical site infection (5.4%),surgical emphysema(3.3%), Pyeothorax and Post-decortication retubation (2.2%). The overall mortality rate was 3.3%.At 3-month follow-up, 91.2% of patients had complete recovery, while 5.5% had mild residual symptoms.Conclusion: Although Bangladesh Shishu Hospital & Institute has shown encouraging results in pediatric thoracic surgery, regular healthcare is hindered by poor infrastructure and delayed diagnosis and referral.Journal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 39-43